A proposed framework for improved software requirements elicitation process in SCRUM: Implementation by a real‐life Norway‐based IT project. Issue 7 (5th February 2020) - Saeeda, Hina; Dong, Junyu; Wang, Yong; Abid, Muhammmad Adil
Abstract: Software requirement engineering (SRE) is the initial stage of the software engineering process and entails several challenges relating to the identification, implementation, evolution, and management of requirements for the development of software systems that meet the desired functionality quality standards. Agile software development (ASD) is a well‐known software development process that follows a lightweight and adaptive methodology to support the incremental development of software systems. Since the ASD follows an adaptive procedure (ie, a flexible, nanostructured, and dynamic approach) of software development, it becomes challenging to perform SRE that follows a structured approach for managing software requirements throughout the life cycle of software development. The primary challenges for SRE, while pursuing an ASD, include, but are not limited to, identification of incomplete requirements, implementation of vague requirements, prioritization of secondary functional requirements, and compromise on users' involvement that negatively impacts the software system's functionality and quality. To overcome these challenges, some of the recent research efforts have focused on managing different phases of SRE during software development using the ASD. However, there is a lack of solutions that provide software engineers/practitioners with a solution. Besides, frameworks to effectively manage all the phases of SRE as per the needs of the ASD are needed. We propose a framework that unifies joint requirements document (JRD) and SCRUM to incrementally (a) identify, (b) implement, (c) evolve, and (d) manage system requirements throughout the software development cycle. We have used the action research method to qualitatively validate the proposed framework based on data and user requirements collected from a product‐focused (multinational) Norway‐based software company. The results of the validation are based on statistical analysis that reflects the usefulness of the proposed framework for SRE in ASD‐based software engineering and development. Future research is the possible application of a machine learning approach (es) in the intended context for agile requirements elicitations.